8y-(6y-3)=

Simple and best practice solution for 8y-(6y-3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8y-(6y-3)= equation:


Simplifying
8y + -1(6y + -3) = 0

Reorder the terms:
8y + -1(-3 + 6y) = 0
8y + (-3 * -1 + 6y * -1) = 0
8y + (3 + -6y) = 0

Reorder the terms:
3 + 8y + -6y = 0

Combine like terms: 8y + -6y = 2y
3 + 2y = 0

Solving
3 + 2y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 2y = 0 + -3

Combine like terms: 3 + -3 = 0
0 + 2y = 0 + -3
2y = 0 + -3

Combine like terms: 0 + -3 = -3
2y = -3

Divide each side by '2'.
y = -1.5

Simplifying
y = -1.5

See similar equations:

| 4x^3+3x^2+3x-1=0 | | 6x+5(20-2x)=12 | | y=lg(x^2-7x+10) | | 3+(-1)*b= | | 0=18000x-450x-5000x-400000-500000 | | x^2-13x+10=0 | | 4x-2xy=7 | | (1)*b= | | 18-27y+10y^2=0 | | (12+3)xy= | | 6xy-3x-2y=55 | | 23423423423423y=238472384672354276345723542365443628723423y | | 123123y+81723981273=283791y+12312 | | -15-(-26)= | | 10=-3x-x^2 | | 4k^2+2k=0 | | 7(6x-8)+5(4-5x)= | | 3-2(5-x)-(4x-1)2= | | 6x-7(x+7)+(2x-7)5= | | 4x+3=x+24 | | x-5+90+2x-5=180 | | x^2-2kx+5k=0 | | 5X-10+4X-10=180 | | x^2+7x=-3.25 | | 6x^2-13x+4=0 | | 3y+6x=wx | | 3h^2+4h=55 | | 5x*4x=80 | | x=25+10+10 | | x+10=x+25+10 | | 10+-0.5n+-2+1p+20-2p=18 | | 8m^2-2m= |

Equations solver categories